Unraveling the response of the apparent temperature sensitivity of ecosystem respiration to rising temperature - Zhentao Liu; Junguo Liu; Deliang Chen (Environmental Research Letters)
Global warming is expected to intensify carbon loss, as ecosystem respiration (RECO) rates increase exponentially with rising temperatures. However, a comprehensive analysis of the response of the apparent temperature sensitivity of RECO ( ${Q_{10}}$ ) to rising temperature is lacking. This study leverages observational data from 254 sites from the FLUXNET2015 and AmeriFlux datasets to address this knowledge gap. We found a strong influence of non-temperature factors on the seasonality of RECO. The similar seasonality of this effect and temperature can lead to underestimating or overestimating ${Q_{10}}$ . In this study, ${Q_{10}}$ was quantified using a temporal moving window and a linear-mixed effect model to account for the effects of non-temperature factors on RECO. Our results show that ${Q_{10}}$ decreases from 1.55 ± 0.24 (mean ± one standard error) at 5 °C to 1.35 ± 0.18 at 25 °C over all sites. The mean slope of ${Q_{10}}$ to temperature across all sites is about −0.02 °C ^−1 . In this study, we found lower values of Q _10 and a lower decreasing rate of Q _10 with rising temperature compared to previous studies. Our study suggests that ${Q_{10}}$ might be systematically overestimated due to the confounding effect of non-temperature factors, potentially leading to overestimated simulation of RECO rate. Our study also emphasizes the necessity of developing a process-based model, rather than simply incorporating the influences of non-temperature factors into ${Q_{10}}$ .